2009
DOI: 10.1002/pon.1510
|View full text |Cite
|
Sign up to set email alerts
|

Sun protection and skin self‐examination in melanoma survivors

Abstract: Patients diagnosed with melanoma are at risk for developing recurrent and second primary disease. Skin self-examination (SSE) and sun protection are standard clinical recommendations to minimize risk. In this study we examined performance of these behaviors in individuals with melanoma drawn from the general population. Potential participants (N=148) with a first primary melanoma diagnosed in 2000 were identified through a population-based cancer registry in New Jersey, USA. One hundred and fifteen individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
93
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 62 publications
13
93
1
2
Order By: Relevance
“…Earlier survey studies showed that the use of sun protection and skin self-examination were both suboptimal in melanoma survivors 14,15 . One population study examined the use of sun protection in early survivors of melanoma and found no difference in their behaviors compared with behaviors in the general population 16 . That result is consistent with our findings and with other behavioral studies comparing all cancer survivors to non-cancer controls.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier survey studies showed that the use of sun protection and skin self-examination were both suboptimal in melanoma survivors 14,15 . One population study examined the use of sun protection in early survivors of melanoma and found no difference in their behaviors compared with behaviors in the general population 16 . That result is consistent with our findings and with other behavioral studies comparing all cancer survivors to non-cancer controls.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these recommendations, many survivors do not practice adequate sun protection [20][21][22], and younger survivors appear to be least likely to follow sun protection recommendations. A recent Childhood Cancer Survivor Study (CCSS) report, which examined several specific sun protection behaviors (e.g., artificial tanning, hat wearing, etc.…”
mentioning
confidence: 87%
“…), showed that despite the increased risk, survivors were only slightly more adherent to sun protection practices compared to their siblings, with women and younger survivors more likely to engage in intentional sun exposure [23]. Mujumdar et al [20] showed that only 23% of melanoma survivors practiced regular sun protection, with youngest patients reporting the lowest adherence. Similarly, National Health Interview Survey data [21] showed that cancer survivors were no more likely to practice recommended sun protection than the general population and that young survivors were the least likely to protect themselves.…”
mentioning
confidence: 95%
“…Además estos estudios ponen de manifiesto que los hábitos de fotoprotección después del diagnóstico no son constantes, ya que un amplio porcentaje de pacientes contesta "a veces" o "con frecuencia" a las preguntas referidas a los comportamientos en fotoprotección 79,117,118 .…”
Section: Discusión -Objetivo Principalunclassified
“…Así, en los pacientes sometidos a una angioplastia tras un infarto agudo de miocardio se ha observado un mayor abandono del hábito tabáquico que en los que no se vieron sometidos a este procedimiento 104 . Sin embargo la influencia de la agresividad terapéutica sobre la fotoprotección en los pacientes con melanoma no ha sido evaluada previamente en la literatura, aunque sí se ha analizado la influencia del índice de Breslow, sin detectarse diferencias significativas en el comportamiento frente al sol en los pacientes con melanomas finos respecto a los que presentaban melanomas gruesos 117 . En los pacientes evaluados en el estudio que presentamos la agresividad terapéutica no influyó en la optimización de la conducta.…”
Section: Discusión -Objetivo Principalunclassified